RESOLUSI KONFLIK PEMBANGUNAN PABRIK SEMEN DI KECAMATAN GUNEM KABUPATEN REMBANG - Khilya Khusnia; Warsito . (Journal of Politic and Government Studies, 2018)
Rembang Regency is located on the north coast of Java Island which is passed by karst mountains of Kendeng Utara, so it has the potential of limestone natural resources that can be utilized as the main raw material of cement making. PT Semen Indonesia (Persero) Tbk plans to mine and establish a cement plant with a capacity of 3,000,000 tons per year in Gunem District, Rembang Regency. The plan to build a cement factory creates social conflict between supportive, rejecting, and governmental citizens. This research seeks to illustrate and analyze the causes of conflict, illustrating the development of conflict and the conflict resolution process undertaken. The research method used qualitative research methods, data collection techniques are done through interviews and documentation. The result of the research shows that the conflict of cement factory development is caused by 4 factors: conflict trigger because there is no socialization of cement factory development. The basic cause is the issue of environmental damage. Factors that mobilize, related to the economy of citizens who mostly work as farmers, as well as the deteriorating factor of environmental permits that violate regulations. The process of conflict resolution is carried out through administrative and judicial processes that are still ongoing. In the conflict of construction of this cement plant there is no effort to resolve the conflict through negotiation, so that there is no conflict of mutual benefit. Recommendation: citizen involvement in every development process is very important to minimize the conflict, negotiation is needed to generate conflict of mutual benefit, and need to be formed BUMDes to overcome the problems and needs of the citizens. Keywords : Conflict, Cement Plant Construction, Conflict Resolution